WHOLE-BODY AND PARTIAL-BODY CRYOTHERAPY: A REVIEW OF MECHANISMS, APPLICATIONS, AND SAFETY - Aleksander Białoń; Paweł Harbut; Dominika Walczak; Weronika Ewa Nowak; Adrian Kruk; Katarzyna Jakubowska; Aleksandra Dorosz; Igor Gawłowski; Aleksandra Miśta; Lidia Jurczenko (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Cryotherapy, encompassing whole-body cryotherapy (WBC) and partial-body cryotherapy (PBC), has gained increasing attention in sports, medicine, rehabilitation, and wellness for its potential anti-inflammatory, analgesic, and recovery-enhancing effects. Originally developed in Japan in the late 1970s for the treatment of rheumatoid arthritis, WBC has since evolved into a multidisciplinary therapeutic modality with a wide range of clinical and non-clinical applications. Materials and Methods: A systematic literature search of PubMed and Embase from 2013–2025 was conducted using the terms “cryotherapy,” “whole-body cryotherapy,” and “cryostimulation.” Results: The evidence suggests that WBC elicits systemic anti-inflammatory effects through modulation of cytokines (e.g., decreased IL-1β, TNF-α, and hsCRP; increased IL-10), enhances antioxidant enzyme activity, and improves markers of oxidative stress. Clinical data further indicate beneficial outcomes in conditions such as rheumatic and osteoarticular diseases, fibromyalgia, multiple sclerosis, mood disorders, chronic pain, and obesity. WBC may also support athletic recovery by reducing muscle soreness and improving performance adaptation. Despite its broad therapeutic potential, contraindications, including cardiovascular, neurological, and cold-related disorders, must be observed. Reported adverse effects are generally mild and transient. Conclusions: Overall, cryotherapy appears to be a promising adjunctive modality, though further controlled studies are warranted to establish standardised treatment protocols and confirm long-term safety and efficacy.